Presenting the agility model of the organization in order to improve the productivity of human resources - Asie Mohmedi; Rashid Zolfaghari; Mahsa Gholam hossein zadeh (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to design the organizational agility model in order to improve the productivity of human resources in Shomal Drilling Company. In terms of purpose, the current research is applicable in the quantitative part, fundamental-exploratory in the qualitative part, and mixed (qualitative-quantitative) in terms of implementation. The statistical population of the research in the qualitative part includes 10 academic specialists, professors and senior managers in the field of human resources and experts in the field of organizational behavior, and sampling was carried out by the theoretical saturation method; and in the quantitative part it includes 2500 people from all employees of Shomal Drilling Company, 333 of whom were selected through the Cochran formula by stratified random sampling method. The research collection tool is a semi-structured interview and a researcher-made questionnaire. Data in the qualitative part analyzed by the coding method and MAXQDA software, and in the quantitative part by SPSS and PLS software. The results in the qualitative section showed that there are 7 components and 52 indicators in the model. The components include 1-causal factors (human and organizational factors); 2- the central phenomenon (organizational agility); 3- strategies (agility strategy); 4- context and facilitator (agility drivers); 5- Obstacles (challenges of human resource management); and 6- Consequences (productivity of human resources). The results in the quantitative part showed that human and organizational factors have an effect on organizational agility, and in this way, it increases the level of the organization's agility strategy and, as a result, the productivity of employees. Also, the results showed that agility drivers and existing challenges in human resource management affect productivity through agility strategy. Extended abstract Introduction Today, productivity and increasing organizational excellence has become one of the most important components of management in large and small organizations. Experienced managers in organizations have now realized that in order to achieve success in the arena of global competition and increase profitability, considering the components related to human and work productivity is very valuable and should always be taken into account (Hojjati & Nasiri, 2020). Today's business environment is full of organizational competition and the smallest slip can lead to the decline of an organization (Hashemzadeh, 2017). In today's competitive world, in order to face the new changes that occur in today's competitive world, organizations should think about adapting to changes (Khakivatan et al, 2021) and seek to take advantage of potential opportunities. One of the parameters proposed to increase flexibility, speed of action, and quality; is organizational agility. Organizational agility is the concept of high adaptability without the need to change. In fact, the organization can create a capacity in its structure and operational methods to create flexibility, change and adaptation to changing conditions without the need to make a series of permanent, mandatory and fundamental changes (Sadiq et al, 2020). Organizational agility refers to an organization's ability to respond quickly and effectively to environmental changes and internal conflicts (Ali Sofi & Salami, 2023). Organizational agility is an organizational capability that must be considered by the managers of educational organizations in order to achieve organizational goals, and has the components of innovation, responsibility, speed in work, low complexity, high quality, flexibility, and readiness to respond to environmental changes, and also is very resistant to environmental problems and challenges (Abolghasem et al., 2018). Therefore, this research seeks to investigate the issue: what model can be designed to make the organization agile in order to improve the productivity of human resources in Shomal Drilling Company? Theoretical framework Organizational agility Agility can be described as a management concept around responding to the turbulent and dynamic market and customer demand, and is not only a solution for the survival of the organization but also an opportunity to achieve sustainable advantage (Tavakoli et al, 2019). Productivity of human resources Productivity means an intellectual point of view and the concept of working and acting intelligently. Productivity can be considered in human resources or capital, and the main and important indicator in this field is undoubtedly human resources and factors affecting it (Rosenzweig, 2020). Kadivar Zinkanloo et al, (2024) investigated the design of organizational resilience development model based on organizational agility components (case study of Sepeh Bank branches in North Khorasan province). The findings of the research show the types of causal factors, phenomenon-oriented, strategies, intervening, contextual and consequences; which according to the research approach, research model at the level of dimensions and components examined and validated in the qualitative stage. Causal factors include flexible organizational culture; central factors include the development of organizational resilience based on organizational agility components; strategic factors include the development of strategies; intervening factors include the change process; background factors include the improvement of processes and communications in the organization; and the outcome includes agility. Ali sofi & Salami (2023) investigated the effect of quantum management skills on susceptibility to change with the mediating role of organizational agility. The findings obtained from the structural equation model showed that the standard coefficient between quantum management was significant on readiness for change (0.19), quantum management on organizational agility (0.58), as well as susceptibility for change and organizational agility (0.64), and the indirect effect of quantum management on change readiness (0.47). Research methodology In terms of purpose, the current research is applicable in the quantitative part, fundamental-exploratory in the qualitative part, and mixed (qualitative-quantitative) in terms of implementation. The statistical population of the research in the qualitative part includes 10 academic specialists, professors and senior managers in the field of human resources and experts in the field of organizational behavior, and sampling was carried out by the theoretical saturation method; and in the quantitative part it includes 2500 people from all employees of Shomal Drilling Company, 333 of whom were selected through the Cochran formula by stratified random sampling method. The research collection tool is a semi-structured interview and a researcher-made questionnaire. Research findings Data in the qualitative part analyzed by the coding method and MAXQDA software, and in the quantitative part by SPSS and PLS software. The results in the qualitative section showed that there are 7 components and 52 indicators in the model. The components include 1-causal factors (human and organizational factors); 2- the central phenomenon (organizational agility); 3- strategies (agility strategy); 4- context and facilitator (agility drivers); 5- Obstacles (challenges of human resource management); and 6- Consequences (productivity of human resources). The results in the quantitative part showed that human and organizational factors have an effect on organizational agility, and in this way, it increases the level of the organization's agility strategy and, as a result, the productivity of employees. Also, the results showed that agility drivers and existing challenges in human resource management affect productivity through agility strategy. Conclusion The current research was conducted with the aim of designing an organizational agility model in order to improve the productivity of human resources in the Northern Drilling Company. The results of this research are in agreement with the results of Kadivar Zinkanloo et al, (2024), Ali sofi & Salami (2023), Ardian et al, (2023), AlNawafleh et al, (2022), Nikkhah (2022), Tashakori et al, (2021), Dehghani Soltani & Shahabipour (2021), Subramony et al, (2021), Khosravipour & Pourjavid (2020), and Moghali & Talebi (2018). Tashakori et al, (2021) showed that "increasing the speed of work-doing", "improving flexibility", "improving organizational competence", and "improving accountability" are requirements for organizational excellence that directly affect organizational agility. According to the results of the research, the following suggestions are presented: 1- Researching and developing by allocating the required resources, creating organizational innovation, using the knowledge management process, empowering employees, and also by recruiting and hiring skilled and specialized personnel, specialized training of employees, creating a strategic vision of the organization and adopting appropriate human resources strategies for the flexibility of employees, creating a culture of change in employees, creating a flexible organizational structure and speed of action in responding to needs, as well as the use of modern technology, agility of organizational processes, and communication with international customers. 2- Paying attention to increasing the speed of work-doing and improving the level of organizational competence of employees, as well as by gaining experience and skills to the flexibility of employees, creating a culture of change in employees, creating a flexible organizational structure and speed of action in responding, as well as the agility of organizational processes and communication with International customers.